Bridging the gap for ice–ocean–ecosystem processes: integrated observing system for the Ross Sea-far East Antarctic Region - Heil, Petra; Stevens, Craig; Lee, Won Sang; Eayrs, Clare; Shin, Hyoung Chul; Alexander, Simon P.; Rack, Wolfgang (Frontiers in Marine Science, 2023)
Our understanding of cross-disciplinary connections for Antarctica’s role in the Earth system remains incomplete, especially around its coastal margins. The focus here is on sea-ice, oceanic, and atmospheric drivers in the joint Ross Sea-far East Antarctic Region (RSfEAR)—one which spans a large longitudinal range and connects a number of ice shelves and polynyas promoting sea-ice growth and underpinning a diverse and rich ecosystem. Here, we present a minireview of recent case studies and how these inform the design for a future integrated ocean–sea ice–atmosphere observing system. The review is built around five themes: i) regional setting, ii) recent studies in the region and current strategies, iii) gap analysis, iv) future observing system design, and v) wider implications for stakeholders.